Impact of Air Quality on Human Health in the Chowk Area of Lucknow: An Analytical Study of Pollution Levels and Health Risks (International Journal of Scientific Research in Science and Technology, 2025)
Air pollution is a significant global health concern impacting millions of people across the world. This paper investigates the sources of air pollution, its harmful effects on human health, and possible solutions to mitigate its impact. By analyzing different pollutants, their origins, and the health risks linked to exposure, this study emphasizes the critical need for robust policies and interventions to reduce air pollution and safeguard public health. The methodology adopted for this study involves collecting air quality data from local monitoring stations and gathering health-related information through hospital records, surveys, and interviews with residents of the Chowk area. Statistical tools, including Analysis of Variance (ANOVA), have been employed to compare pollution levels in Chowk with other areas of Lucknow, confirming significantly higher pollutant concentrations in the study area. The results indicate that PM2.5 and PM10 levels frequently exceed the permissible limits set by the National Ambient Air Quality Standards (NAAQS), especially during peak traffic hours. The analysis also highlights a strong positive correlation between pollutant levels and the prevalence of respiratory and cardiovascular diseases among the residents. This research paper investigates the impact of air quality on human health in the Chowk area of Lucknow, a highly polluted commercial zone. The study focuses on the levels of air pollutants such as PM2.5, PM10, Nitrogen Dioxide (NO2), and Ozone (O3) and their correlation with respiratory and cardiovascular diseases reported by residents. The paper also emphasizes the need for better air quality management and policy implementations to mitigate adverse health effects.